PENERAPAN PROJECT PENGUATAN PROFIL PELAJAR PANCASILA TEMA KEARIFAN LOKAL DALAM MELESTARIKAN KEBUDAYAAN BANTEN - Aryanti Dwi Untari; Ifah Muzdalifah (Pro Patria: Jurnal Pendidikan, Kewarganegaraan, Hukum, Sosial, dan Politik, 2024)
ABSTRACT In general, the curriculum is a set of subjects consisting of study programs provided by an educational institution, in which there are learning designs, content arrangements, and learning materials that will be used as guidelines in teaching and learning activities. This research uses qualitative methods because the focus of the problem taken is about the Application of the Project for Strengthening the Profile of Pancasila Students with the Theme of Local Wisdom in Preserving Banten Culture at SMAN 6 Serang City. The methods used to collect data in this study were observation, interviews, and documentation. The research location is located at SMAN 6 Serang City. Based on the results of research at SMA Negeri 6 Kota Serang, the implementation of the Pancasila student profile strengthening project with the theme of local wisdom is a project activity compiled by the school, first there is preparation, namely in the form of preparation and creation of a project module to strengthen the Pancasila student profile, the second is the core activity of the project which begins with the stages of the project There are three stages, namely inspiring, creating, and dedicating. The implementation of the project to strengthen the profile of Pancasila students with the theme of local wisdom is inseparable from the important role of teachers as project facilitators because whether or not students are able to preserve Banten culture in projects with the theme of local wisdom is determined by the facilitator, and facilitators are given the task of directing, facilitating and motivating students to be creative and innovative in learning.